2013
DOI: 10.1097/ccm.0b013e318287f6e7
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Distribution of Tidal Ventilation in Acute Respiratory Distress Syndrome

Abstract: In patients with acute respiratory distress syndrome undergoing pressure support ventilation, higher positive end-expiratory pressure and lower support levels increase the fraction of tidal ventilation reaching dependent lung regions, yielding more homogeneous ventilation and, possibly, better ventilation/perfusion coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 27 publications
4
89
0
Order By: Relevance
“…A similar observation was made by Blankmann et al showing that lower inspiration support, both in PCV and neurally adjusted ventilatory assist mode (NAVA), provided better conditions of ventilation in dependent regions [24]. EIT imaging demonstrated that improvement of aeration of dependent lung sectors could be achieved by recruitment with positive end-expiratory pressure or by increased involvement of the diaphragm in initiation of inspiration [23,24].…”
Section: Eit To Monitor Regional Ventilation In Ardssupporting
confidence: 72%
“…A similar observation was made by Blankmann et al showing that lower inspiration support, both in PCV and neurally adjusted ventilatory assist mode (NAVA), provided better conditions of ventilation in dependent regions [24]. EIT imaging demonstrated that improvement of aeration of dependent lung sectors could be achieved by recruitment with positive end-expiratory pressure or by increased involvement of the diaphragm in initiation of inspiration [23,24].…”
Section: Eit To Monitor Regional Ventilation In Ardssupporting
confidence: 72%
“…EIT data were generated by application of small alternate electrical currents rotating around patient's thorax and stored for offline analysis, as previously described (16)(17)(18). Airway pressure, flow, and volume tracings were continuously recorded.…”
Section: Eit Monitoringmentioning
confidence: 99%
“…For this purpose, we assessed regional dynamic lung imaging by electrical impedance tomography (EIT): a noninvasive, radiation-free, bedside lung imaging technique, which tracks changes in regional lung impedance, corresponding to changes in regional gas content (16)(17)(18). By EIT, we measured the changes induced by Sigh on regional Vt, regional EELV, and the heterogeneity of ventilation distribution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In ARDS patients, EIT can visualize directly and non-invasively the effects of mechanical ventilation at the bedside, potentially helping the clinician to titrate ventilation parameters (52,53). In ARDS, interstitial oedema increases the effects of gravity dependent lung regions, and EIT can detect such loss of aeration along with compensatory increases in ventilation of ventral regions (49,50,53).…”
Section: Eitmentioning
confidence: 99%